Mental Health problem and Sustainable Development in India: An Overview - Ahmed, Aijaz (Indian Journal of Community Health, 2019)
Mental health is an emerging problem in the world, particularly in the developing countries like India, which is a big challenge for the sustainable human development. Health is a vital requirement for sustainable human development, and there can be no health without mental health. The role of mental health is very important in accomplishing social inclusion and equity. It also plays a vital role in acquiring universal health coverage, access to justice and human rights, and sustainable economic development. The World Health Organisation (WHO) defines health is not only the absence of disease but it implicates the physical, social, spiritual and mental health (Park, 2015:12-13). Since primordial eras, India, has emphasised on the health of its citizens and has underlined the need for a physically and mentally healthy society. In the new SDGs, the UN has lastly demarcated that mental health is one of the most universal development precedence, and set the scene for an ambitious plan to tackle the world’s challenges in the coming 15 years. WHO has also projected two indicators to strengthen mental health in the SDGs, which are fully aligned with the WHO Global Mental Health Action plan, both within the health goal: (1) suicide rate; and (2) service coverage (proportion treated) of persons with severe mental illness (World Health Organization, 2015). This paper is based on secondary data. The main thrust of this paper was to explore the frequency and pattern of mental disorder and its impact on families or household. This paper also analysed the mental morbidity rate and its cause in India. The findings demonstrated that 13.7 per cent of India’s general population has various mental disorders; 10.6 per cent of them need instant mediations. Whereas, almost 10 per cent of the population has common mental disorders, 1.9 per cent of the masses suffer from severe mental disorders. The result shows that the frequency of schizophrenia is more in urban metros then rural counterparts. The occurrence of mental illness is found to be very high in urban centres, where there is a higher prevalence of schizophrenia, mood disorders and neurotic or stress-related disorders.